PENGARUH HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA TOKO MS COLLECTION DI KABUPATEN SITUBONDO - Abdus Salam; Ediyanto Ediyanto; Lita Permata Sari (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
In the era of increasingly fierce business competition, price, product quality, and service quality have become important elements in building customer satisfaction. This study aims to analyze the influence of price, product quality, and service quality on customer satisfaction through purchase decision as an intervening variable at MS Collection Store in Situbondo Regency. This research is an explanatory study with a quantitative approach. The population of this research is the customers of MS Collection Store, with the sampling technique using purposive sampling. Data analysis was conducted using IBM SPSS Statistic 22 with Structural Equation Modeling – Partial Least Square (PLS-SEM) through Smart PLS 3.2 software. The results of the hypothesis testing using Smart PLS 3.2 show that Price has a positive influence on Purchase Decision but the effect is not significant, Price has a positive influence on Customer Satisfaction but the effect is not significant, Product Quality has a positive influence on Purchase Decision but the effect is not significant, Product Quality has a positive influence on Customer Satisfaction but the effect is not significant, Service Quality has a positive and significant influence on Purchase Decision, Service Quality has a positive influence on Customer Satisfaction but the effect is not significant, Purchase Decision has a positive influence on Customer Satisfaction but the effect is not significant, Price has a positive influence on Customer Satisfaction through Purchase Decision but the effect is not significant, Product Quality has a positive influence on Customer Satisfaction through Purchase Decision but the effect is not significant, Service Quality has a positive influence on Customer Satisfaction through Purchase Decision but the effect is not significant.